IMPORTANCE OF DIFFERENT METHODS TO TEACH WRITING SKILLS TO EFL LEARNERS (Academia Science Repository, 2023)
The ability to write is crucial in our everyday lives as it facilitates communication within our communities. Additionally, it plays a crucial role in the development and teaching of language. As a result, teaching writing is vital, especially for those learning English as a second language in Uzbekistan. This article is devoted to clarify effective methods to teach writing skills.